What can we learn from privately held firms about executive compensation? - Rebel A. Cole; Hamid Mehran (Federal Reserve Bank of New York, 2008)
This study examines the determinants of CEO compensation using data from a nationally representative sample of privately held U.S. corporations. We find that (i) the pay-size elasticity is much larger for privately held firms than for the publicly traded firms on which previous research has almost exclusively focused; (ii) executives at C-corporations are paid significantly more than executives at S-corporations; (iii) executive pay is inversely related to CEO ownership; (iv) executive pay is inversely related to leverage; and (v) executive pay is related to a number of CEO characteristics, including age, education, and gender. Executive pay is inversely related to CEO age and positively related to educational attainment. Finally, female executives are paid significantly less than their male counterparts.
Keywords: H24; H25; G32; J33; 330; Compensation; organizational form; taxes; ownership; education; gender; Führungskräfte; Vergütungssystem; Lohndifferenzierung; Organisationsstruktur; Eigentümerstruktur; USA